An optical biosensing strategy based on selective light absorption and wavelength filtering from chromogenic reaction - Chun, Hyeong Jin; Han, Yong Duk; Park, Yoo Min; Kim, Ka Ram; Lee, Seok Jae; Yoon, Hyun C. (Materials, 2018)
To overcome the time and space constraints in disease diagnosis via the biosensing approach, we developed a new signal-transducing strategy that can be applied to colorimetric optical biosensors. Our study is focused on implementation of a signal transduction technology that can directly translate the color intensity signals-that require complicated optical equipment for the analysis-into signals that can be easily counted with the naked eye. Based on the selective light absorption and wavelength-filtering principles, our new optical signaling transducer was built from a common computer monitor and a smartphone. In this signal transducer, the liquid crystal display (LCD) panel of the computer monitor served as a light source and a signal guide generator. In addition, the smartphone was used as an optical receiver and signal display. As a biorecognition layer, a transparent and soft material-based biosensing channel was employed generating blue output via a target-specific bienzymatic chromogenic reaction. Using graphics editor software, we displayed the optical signal guide patterns containing multiple polygons (a triangle, circle, pentagon, heptagon, and 3/4 circle, each associated with a specified color ratio) on the LCD monitor panel. During observation of signal guide patterns displayed on the LCD monitor panel using a smartphone camera via the target analyte-loaded biosensing channel as a color-filtering layer, the number of observed polygons changed according to the concentration of the target analyte via the spectral correlation between absorbance changes in a solution of the biosensing channel and color emission properties of each type of polygon. By simple counting of the changes in the number of polygons registered by the smartphone camera, we could efficiently measure the concentration of a target analyte in a sample without complicated and expensive optical instruments. In a demonstration test on glucose as a model analyte, we could easily measure the concentration of glucose in the range from 0 to 10 mM.
Keywords: Biochemical assay; Chromogenic reaction; Liquid-crystal display panels; Naked-eye detection; Point-of-care testing; Soft material; Spectral correlation; Wavelength filtering; Chromogenic biochemical assay; Naked-eye detection; PDMS optical filter; Point-of-care testing; Smartphone-based biosensor; Soft material-based channel